Preferensi Mahasiswa Terhadap Makanan Tradisional dengan Makanan Cepat Saji dari segi Pemahaman Bahan Kimia - Annisa Nurcahya Frysilia Hidayat; Andini Dwi Dinanti; Keyla Deandra Fathiyyah (International Forum of Researchers and Lecturers, 2024)
A person's preferences in choosing food are very subjective. Currently, many young people prefer fast food or modern food over traditional food, because they think that modern food is prestigious food, without considering that fast food contains more chemicals which have side effects on health. Method Data collection is by using a quantitative approach to obtain data in the form of numbers or statistics. where data collection was carried out using a questionnaire whose contents were statements that could measure consumer perceptions. It turned out that after research was conducted on 23 students, 50% of these students consumed fast food more often than traditional food even though their understanding of chemicals and their effects was quite high. beside him. Judging from the results, 95.8% of the students knew that fast food contains more dangerous chemicals than traditional food. A high level of understanding of chemicals apparently does not affect a person's preference for the food they consume, because a person still prioritizes desires. compared to needs, namely the need for food with few chemicals for health.